Ownership in Name, But not Necessarily in Action; Comment on "It's About the Idea Hitting the Bull's Eye": How Aid Effectiveness Can Catalyse the Scale-up of Health Innovations" - Melisa Martinez-Alvarez (Kerman University of Medical Sciences, 2018)
A recently-published paper by Wickremasinghe et al assesses the scalability of pilot projects in three countries using the aid effectiveness agenda as an analytical framework. The authors report uneven progress and recommend applying aid effectiveness principles to improve the scalability of projects. This commentary focuses on one key principle of aid effectiveness - country ownership; it describes difficulties in defining and achieving it, and provides practical steps donors and recipient governments can take to move forward towards country ownership.